2000
DOI: 10.1111/j.1550-7408.2000.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Identification of Hypermastigotes, Pseudotrichonympha, Spirotrichonympha, Holomastigotoides, and Parabasalian Symbionts in the Hindgut of Termites

Abstract: The phylogenetic diversity of parabasalian flagellates was examined based on the sequences of small subunit ribosomal RNA genes amplified directly from the mixed population of flagellates in the hindgut of lower termites. In total, 33 representative sequences of parabasalids were recovered from eight termite species. Fluorescent-labeled oligonucleotide probes specific for certain sequences were designed and used for the in situ identification of parabasalian species by whole-cell hybridization. The hypermastig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 27 publications
7
83
1
Order By: Relevance
“…Furthermore, approximately 18z of the clones cannot be readily assigned to any recognized group of Bacteria. The analogous culture-independent approaches have been successfully applied, in various termite species, to the studies of their gut microbial community of ‰agellated protists, 3) spirochetes, 4,5) methanogenic Archaea, [6][7][8] and diazotrophs. 9,10) These studies revealed that the majority of the gut community consists of novel and yet-uncultured species previously unknown to microbiologists.…”
mentioning
confidence: 99%
“…Furthermore, approximately 18z of the clones cannot be readily assigned to any recognized group of Bacteria. The analogous culture-independent approaches have been successfully applied, in various termite species, to the studies of their gut microbial community of ‰agellated protists, 3) spirochetes, 4,5) methanogenic Archaea, [6][7][8] and diazotrophs. 9,10) These studies revealed that the majority of the gut community consists of novel and yet-uncultured species previously unknown to microbiologists.…”
mentioning
confidence: 99%
“…Culture-independent molecular studies, however, have been successfully applied to the gut dwellers of termites (for reviews, see reference 26); these studies were mainly molecular phylogenetic analyses. They revealed unexpected diversity among termite gut protists (12,(27)(28)(29). Genes involved in cellulose decomposition have also been identified previously (references 18 and 36 and references therein).…”
mentioning
confidence: 82%
“…The flagellated protists in the gut of C. formosanus comprise exclusively the three parabasalian species P. grassii, Holomastigotoides mirabile, and Spirotrichonympha leidyi (28,29). P. grassii belongs to the family Eucomonymphidae, while the latter two belong to the family Spirotrichonymphidae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations